Smartpreneur 5.0: Building a Digital Generation with an Islamic Entrepreneurial Spirit Among the Youth of PERMAI Malaysia - K, M. Yusuf; Alam, Syamsu; Rahmah, Syahidah; Wahyuni, Sri; Fatimah, Emi Sri Rahayu (PT Inovasi Pratama Internasional, 2025)
Smartpreneur 5.0 Programme: Building a Digital Generation with an Islamic Entrepreneurial Spirit the PERMAI Malaysia Youth Generation was implemented as an effort to improve digital-based entrepreneurial literacy based on sharia values. This activity was designed through stages of preparation, material delivery, workshops, and evaluation with a participatory approach. The evaluation, which used pre-tests and post-tests, showed a significant increase in participants' understanding of five key indicators, namely the basics of Islamic entrepreneurship, digital business concepts, digital marketing strategies, Islamic financial management, and digital business idea design. These results demonstrate the effectiveness of the training methods in strengthening the digital entrepreneurship understanding and skills of the younger generation. In addition to increasing knowledge, this activity also produced several important outputs, including training modules as learning references, innovative digital-based Islamic business idea designs, participants' digital business accounts as real implementations, and activity documentation that can be used as a reference for similar programmes in the future. Furthermore, the impact of the activity did not stop at the cognitive aspect, but also touched on the character dimension, namely shaping a creative, innovative entrepreneurial spirit based on Islamic ethics. Thus, Smartpreneur 5.0 succeeded in achieving its planned objectives while making a real contribution to producing a highly competitive young generation with a strong spiritual foundation